2013
DOI: 10.1002/cmmi.1580
|View full text |Cite
|
Sign up to set email alerts
|

In vivo visualization of single native pancreatic islets in the mouse

Abstract: The purpose of this study was to investigate the potential of a novel targeted contrast agent (CA) for the in vivo visualization of single native pancreatic islets, the sites of insulin production, in the pancreas of mice using magnetic resonance imaging (MRI). The CA for intravenous administration was composed of the β-cell-specific single-chain antibody fragment, SCA B1, and ferromagnetic carbon-coated cobalt nanoparticles. MRI experiments were performed at 7, 9.4 and 16.4 T in excised organs (pancreas, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…The data provide a significant step towards the validation of a probe monitoring the effect of candidate treatments in a pre-clinical setting, assuming that the expression of GLP-1rs is not altered under different glycaemic conditions [ 43 ]. Such pre-clinical studies should further benefit from the exquisite resolution achieved with high magnetic field MRI, which now allows for the visualisation of individual islets within an intact pancreas [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data provide a significant step towards the validation of a probe monitoring the effect of candidate treatments in a pre-clinical setting, assuming that the expression of GLP-1rs is not altered under different glycaemic conditions [ 43 ]. Such pre-clinical studies should further benefit from the exquisite resolution achieved with high magnetic field MRI, which now allows for the visualisation of individual islets within an intact pancreas [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the search for alternatives, several studies have investigated MRI [ 20 22 ], a method that does not involve ionising radiation. The modality provides for an unsurpassed anatomical visualisation of soft tissues, including individual islets in experimental models when high magnetic fields are used [ 21 , 23 ]. Still, MRI has a significantly lower sensitivity than either PET or SPECT, and hardly allows for an absolute quantitative evaluation of the signal [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that, using the methods presented in this report, this size and spatial variation is readily captured. Further, the murine pancreas is a complex structure and differs significantly from that of other mammals, including man (Islam 2010; Balla et al 2013). The mouse pancreas is sparse and extends along the big curvature of the stomach, contacting its thick tail (left lobe) with the spleen, whereas while the human pancreas topography is similar, it is a more compact gland and its tail is the thinner part of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…IC2, a rat monoclonal IgM Ab, which targets sphingomyelin on the β‐cell surface . Single‐chain antibodies (SCA), such as SCA‐B1 . The target of SCA‐B1 is not known but was shown specific for β cells and suitable for MRI, after coupling it with highly magnetic cobalt nanoparticles . Less specifically, hydroxy‐tryptophan targets the serotonergic innervation, which is present in all the endocrine cells of the pancreas ; however, in spite of their wide expression, this probe appeared to show a correlation between β‐cell mass and pancreatic signal in STZ‐treated rats and have been able to differentiate people with T1DM from healthy people Somatostatin receptors were also proposed as a target for imaging probes to monitor β‐cell mass. Thus, Sako et al.…”
Section: Tools and Targets For Imaging Of β‐Cell Massmentioning
confidence: 99%
“…• Single-chain antibodies (SCA), such as SCA-B1 [107]. The target of SCA-B1 is not known but was shown specific for cells and suitable for MRI, after coupling it with highly magnetic cobalt nanoparticles [34].…”
Section: 'Functional' -Cell Massmentioning
confidence: 99%